Pengaruh Latihan Resistance Band terhadap Kecepatan Tendangan Sabit pada Atlet Pencak Silat PSHT Kecamatan Betung - Tri Rahmat Rezeki; Mutiara Fajar; Puput Sekar Sari (Pusat Riset dan Inovasi Nasional, 2025)
Through field observations, it was found that the students' ability to perform crescent kicks had not shown good speed, to obtain the ability to kick with speed, resistance band training was given. The purpose of this study was to determine the effect of resistance band training on the ability to kick crescents in pencak silat athletes at the PSHT school in Betung District. This research method is an experimental method with a one group pretest-posttest research design. The population of PSHT athletes was 16 people with the use of samples taken from the total population. Data collection used a crescent kick ability test on petching for 10 seconds. Data analysis used paired sample t-test analysis via SPSS. Based on the information from the results of data analysis through hypothesis testing, the study concluded that there was an effect of resistance band training on the results of crescent kicks in pencak silat athletes at PSHT in Betung District